Termites as Soil Engineers: A Study on Organic Carbon and Nutrient Dynamics using Baiting Techniques in Tropical Forest Ecosystem - Febriani, Sri Rezeki; Ariyanto, Dwi Priyo; Cahyono, Ongko; Tarmadi, Didi; Wikantyoso, Bramantyo; Himmi, Setiawan Khoirul; Zaki, Muhamad Khoiru (Bogor Agricultural University, Indonesia, 2026)
This study explores how termite activity affects soil chemistry, those are Soil Organic Matter (SOC) and nutrient dynamics in pine and mahagony forest of varying ages in the Bromo Forest, Indonesia. Termite activity was assessed using wooden poles placed in PVC pipes as bait, which also served for soil sampling. The results showed significant differences in SOC and total NPK levels among different pole damage classes in each forest. The highest values were observed in pole damage class 4. Termite-influenced soil, especially those affected by the genera Macrotermes sp., Microtermes sp., and Schedorhinotermes sp., showed the highest concentrations of SOC and NPK (4.97%, 0.51%, 15.42 mg/100 g, and 45.9 mg/100 g, respectively). The termite diversity index showed moderate diversity in all pine forests and low diversity in mahogany forests. The termite diversity index indicated moderate diversity in pine forests and low diversity in mahogany forests, likely influenced by bait type. These results demonstrate that termite activity significantly enhances soil nutrient content and can be used as an indicator of soil fertility status in tropical forest ecosystems.